Effects of Thyroid Hormones on Electrical and Mechanical Parameters of the Heart - Dzhumaniiazova, I. K.; Smirnova, Olga V. (Human Physiology, 2020)
Abstract: Despite the fact that effects of thyroid hormones were noticed back in the 80s, the underlying molecular mechanisms have not yet been elucidated. Current review summarizes years of investigations upon molecular targets for the action of thyroid hormones, leading to changes in the electrical and mechanical activity of the heart; changes in hemodynamics, affecting the functioning of the heart muscle, are also touched.
CRIS-Team Scopus Importer:2023-04-20
Keywords: cardiomyocytes; fibroblasts; ion currents; macrophages; the heart; thyroid hormones